Analisis Strategi Fundraising Zakat oleh Baznas Kabupaten Purwakarta terhadap Potensi Zakat Maal Baznas Kabupaten Purwakarta - Naufal Aqil Anshari; Maman Surahman; Zaini Abdul Malik (UNISBA Press, 2024)
Abstract. For Muslims, zakat, infaq and sadaqah are familiar concepts. Muslims have known and practiced zakat, infaq and shadaqah for a long time. Infaq and shadaqah always appear when discussing zakat. Although there are other sources of funds that can be collected, such as infaq, sadaqah, waqf, wills, grants, and the like, zakat is one of the tools used to combat poverty. It is very important to understand zakat to prevent situations of money theft and other dangerous activities. This research aims to analyze the zakat fundraising strategy by the Purwakarta Regency Baznas towards the Purwakarta Regency Baznas maal zakat. The potential for zakat in Purwakarta district is 350 billion. The research method used in this research is a qualitative method. Based on the graph of mall zakat income, it can be concluded that the implementation of the fundraising strategy is less effective. This can be seen from the data which shows that even though various methods of collecting funds have been implemented, such as collaboration with government and financial agencies through the Zakat Collection Unit (UPZ), placement of charity boxes in strategic locations by the retail division, as well as organic use of social media, the results obtained does not show a significant or consistent increase in mall zakat income. The graph shows fluctuations that may be caused by a lack of innovation in fundraising methods, limitations in the use of paid advertising on social media, and possible obstacles in coordination with various agencies and organizations. Thus, it is necessary to evaluate and improve fundraising strategies to achieve more optimal results. Abstrak. Bagi umat Muslim, zakat, infak, dan shadaqah merupakan konsep yang tidak asing lagi. Umat Muslim telah mengenal dan mempraktekkan zakat, infaq, dan shadaqah sejak lama. Infaq dan shadaqah selalu muncul ketika membahas tentang zakat. Meskipun ada sumber dana lain yang dapat dikumpulkan, seperti infaq, shadaqah, wakaf, wasiat, hibah, dan sejenisnya, zakat adalah salah satu alat yang digunakan untuk memerangi kemiskinan. Sangat penting untuk memahami zakat untuk mencegah situasi pencurian uang dan kegiatan berbahaya lainnya Penelitian ini bertujuan untuk menganalisis strategi fundraising zakat oleh Baznas Kabupaten Purwakarta terhadap zakat maal Baznas Kabupaten purwakarta. Potensi zakat di kabuaten Purwakarta sebesar 350 Milyar. Metode penelitian yang digunakan dalam penelitian ini adalah metode kualitatif. Berdasarkan grafik pendapatan zakat mal, dapat disimpulkan bahwa pelaksanaan strategi fundraising tersebut kurang efektif. Hal ini terlihat dari data yang menunjukkan bahwa meskipun telah diterapkan berbagai metode pengumpulan dana, seperti kerja sama dengan instansi pemerintah dan keuangan melalui Unit Pengumpulan Zakat (UPZ), penempatan kotak amal di lokasi strategis oleh divisi retail, serta penggunaan media sosial secara organik, hasil yang diperoleh tidak menunjukkan peningkatan yang signifikan atau konsisten dalam pendapatan zakat mal. Grafik tersebut memperlihatkan fluktuasi yang mungkin disebabkan oleh kurangnya inovasi dalam metode pengumpulan dana, keterbatasan dalam penggunaan iklan berbayar di media sosial, dan kemungkinan adanya kendala dalam koordinasi dengan berbagai instansi dan organisasi. Dengan demikian, perlu dilakukan evaluasi dan perbaikan strategi fundraising untuk mencapai hasil yang lebih optimal.